Польский компонент в поэтике Иосифа Бродского - Barasz, Olga (Acta Polono-Ruthenica, 2018)
The article deals with the influence of Polish literature on the creative work of Joseph Brodsky. The relation of Brodsky’s poetry to Polish sources is shown on different text levels: phonetic, lexical, metrical and intertextual. It is maintained that some elements of Brodsky’s poetic technique are rooted in the works by M. Pawlikowska-Jasnorzewska, L. Pasternak, J. Iwaszkiewicz and M. Hlasko.